Acceptance Analysis Of Mobile Learning Using The Unified Theory Of Acceptance And Use Of Technology (UTAUT): The Case Of Asynchronous Learners - A. Amahan, Pilita; DIT, DIT (International Journal of Educational Research & Social Sciences, 2023)
The purpose of this study is to assess the information technology students’ acceptance of and intention to use mobile learning applications using the Unified Theory of Acceptance and Use of Technology (UTAUT) model. The study, which involved a first-year through fourth –year and even graduate students from the information technology department, was carried out from January to June 2022. Eighty volunteers participated in the study and completed the self-made questionnaire based on the UTAT model’s five constructs: performance efficiency (PE), effort expectancy (EE), social influence (SI), facilitating conditions (FC), and behavioral intention (BI). Using the Cronbach’s alpha coefficient, the questionnaire’s acceptability and reliability were also evaluated. The association between the five factors and the intention to adopt mobile learning was also evaluated using regression analysis. The study’s final score of α=0.080619 suggests that the contracted questionnaires were good and acceptable. Four theories were put to the test, and the results indicate a favorable impact on the behavioral intention to utilize mobile learning applications. Future research should reevaluate the UTAUT model among students who are not studying computer technology when an asynchronous style of learning is also relevant.